The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/eos.12082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hyaluronan and superficial zone protein in synovial membrane cells modulated by fluid flow

Abstract: Hyaluronan (HA) and superficial zone protein (SZP) distribute in joint structures and play a crucial role in joint lubrication. The aim of this study was to examine the effect of fluid flow on the synthesis of both HA and SZP in synovial membrane cells. Shear stress was applied by fluid flow to the rabbit synovial membrane cell line, HIG-82. The mRNA levels of HA synthase 2 (HAS2) , HA synthase 3 (HAS3), and SZP were examined by real-time PCR. The levels of HA and SZP protein were determined by sandwich ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…As HYAL1 and HYAL2 mRNA levels were upregulated in the presence of IL‐1β, resulting in enhanced HYAL activity 18 . High‐magnitude shear stress decreased expression of both HAS2 and HAS3, accompanied by reduced HA synthesis 19 . A single intra‐articular injection of diclofenac etalhyaluronate (SI‐613) was capable of inducing the production of high molecular weight HA in synoviocytes from OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…As HYAL1 and HYAL2 mRNA levels were upregulated in the presence of IL‐1β, resulting in enhanced HYAL activity 18 . High‐magnitude shear stress decreased expression of both HAS2 and HAS3, accompanied by reduced HA synthesis 19 . A single intra‐articular injection of diclofenac etalhyaluronate (SI‐613) was capable of inducing the production of high molecular weight HA in synoviocytes from OA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis, cell surface binding and actin reorganization together may affect how FLS synthesize other molecules beyond the ECM proteins or inflammatory factors studied here in response to physical stimuli presented to FLS in the synovial joint environment (e.g. fluid shear or mechanical stretch) 4850 .…”
Section: Discussionmentioning
confidence: 99%
“…HA is reported to protect against apoptosis and to promote survival in various types of cells, including granulosa cells (44), articular chondrocytes (45,46), and human aortic smooth muscle cells (37). In contrast, other studies showed that HA treatment induces cell death in cultured human gingival fibroblasts (47) and lymphoma cell lines (48). Thus, the regulatory effect of HA upon cell viability appears to depend upon cell context, even when controlling for the size of HA, because high molecular weight HA has been shown to either promote cellular survival (37) or induce cell death (49) in different cell types.…”
Section: Discussionmentioning
confidence: 99%